Review of Artifacts and Related Processing in Ophthalmic Optical Coherence Tomography Angiography (OCTA) - Zhefan Lin; Yitao Hu; Gongpu Lan; Jingjiang Xu; Jia Qin; Lin An; Yanping Huang (Photonics)
Optical coherence tomography angiography (OCTA) is a non-invasive imaging modality that can provide rich three-dimensional microvascular information of fundus in ophthalmic imaging. However, various imaging artifacts may be generated during OCTA data acquisition and processing, originating from a number of factors such as multiple light scattering, tissue motion, improper device operation and signal processing algorithms. Artifacts can detrimentally affect the qualitative interpretation of clinical pathologies and quantitative evaluation of vasculature parameters. This article firstly introduces the OCTA acquisition process and sources of artifacts, and then describes four different categories of artifacts in detail, mainly including light propagation and signal intensity-related artifacts, tissue motion artifacts, improper operation artifacts, and signal processing-related artifacts. Corresponding methods for the identification and processing of these artifacts are also presented. Furthermore, this article also details some recent progress in leveraging artificial intelligence (AI) technology in the identification and suppression of artifacts, showcasing its potential as a powerful tool in OCTA artifact processing. The development of artifact suppression techniques enables OCTA to reliably evaluate fundus diseases and monitor their progression. This development facilitates broader and deeper applications of OCTA in both research and clinics of ophthalmology.